The intercultural speaker across time: a study of Tunisian EFL textbooks. Issue 7 (3rd October 2022) - Abid, Nadia; Moalla, Asma
ABSTRACT: This paper examines the extent to which the intercultural speaker is promoted through intercultural contacts in five Tunisian EFL textbooks produced in five different periods in the history of English language teaching in Tunisia. Using content analysis, the study evaluated the textbooks' representation of intercultural contacts in texts and activities. The results revealed that intercultural contacts were limited in frequency and variety in both contents and activities, and that textbooks were mainly meant to teach language forms and language skills. Despite being designed in different periods and using different teaching methods, textbooks did not differ in their representation of contacts and their potential to develop the intercultural speaker's competencies in learners. It is suggested that more importance should be given to intercultural contacts in the current textbook series to make them more responsive to learners' increasing needs for intercultural communication skills.